State and prospects of studying of some Kazakhstan types of Polygonaceae Juss family (Experimental biology, 2016)
The review of a state and prospects of studying of the Kazakhstan types of the Polygonum L. species are given in article. The analysis of data on medicinal use of plants, about productivity, operational quantities and possible annual preparations of the most perspective types for introduction to medicine is resulted in paper. Results of comparative phytochemical research of the main groups of biologically active substances of 4 Polygonum species depending on a growth place are for the first time presented. The most perspective places of their possible industrial preparations are experimentally established.
Keywords: Polygonaceae Juss.; productivity; operational quantities; phytochemical analysis.